2015
DOI: 10.1155/2015/579486
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated BIM System to Track the Time and Cost of Construction Projects: A Case Study

Abstract: Many construction projects suffer from poor design and from inconsistent time and cost management. This situation has led to rethinking of the industry’s performance and how it could be improved. Technology is breaking through design and management practices. Earned value management (EVM) enables better management of time and cost constraints. Building Information Modeling (BIM) is recognized to improve the planning and realization of a construction project. The present paper proposes an integrated time and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 20 publications
(19 reference statements)
1
23
0
1
Order By: Relevance
“…This tool includes just the planning phase of building projects, because its interface did not develop a cost and time control module. (Jrade and Lessard, 2015) developed ITCMS, which is able to integrate both budget and schedule, adding a time and cost control through the EVM technique. However, the use of different tools for construction project management causes data reprocessing and leaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tool includes just the planning phase of building projects, because its interface did not develop a cost and time control module. (Jrade and Lessard, 2015) developed ITCMS, which is able to integrate both budget and schedule, adding a time and cost control through the EVM technique. However, the use of different tools for construction project management causes data reprocessing and leaks.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above, authors like (Jrade and Lessard, 2015) propose an integrated time and cost management system, called (ITCMS). It is composed by an EVM platform developed in Microsoft Excel and MS Project, which synchronizes the construction model with the project's time and cost parameters.…”
Section: Introductionmentioning
confidence: 99%
“…EVM finds application in very varied contexts. It is a technique traditionally applied in the construction industry [28][29][30], where it has been regularly and successfully applied. But it has also been applied in different highly specialized contexts with a large number of special features and needs.…”
Section: Evm Technique and Earned Schedule The Earned Valuementioning
confidence: 99%
“…BIM automatically presents data both visually and analytically, information is clearer and easier to understand, and 4D models serve as platform for detection of potential conflicts and risk analysis [10] Having observed that an intrinsic limit of 4D visualization in BIM models is the lack of economic features, we propose system to integrate BIM technology and EVM, following Haque [10] and Jrade and Lessard's intuition [11]. The basis of the study comes from the idea of Construction Site Information Model (Co.S.I.M.)…”
Section: Literary Reviewmentioning
confidence: 99%